Problematika dan Solusi Manajemen Pembelajaran PAI di Perguruan Tinggi Keagamaan Islam - Fathiyatul Haq Mai Al Mawangir (LPPM Institut Agam Islam Nahdlatul Ulama (IAINU) Kebumen, 2023)
This paper is motivated by problems in the management of PAI learning at PTKIwhich find problems from various aspects of the curriculum, lecturers, and learningprocess to student input that do not meet the minimum standards. This then requires asolution so that the objectives of PAI learning at PTKI can be achieved. The researchmethod used in this study is a qualitative method with a library approach.The results in this study to become a solution for the problems faced by lecturers atPTKI are that lecturers must master plan fullness, provide intrinsic motivation, be ableto carry out internalized evaluations, openness to experience, be flexible in learning,loyal, and have autonomy in determining learning forms. All of this will be successful ifit is supported by a curriculum that is anticipatory and adaptive to changing times andmakes students want to apply what they have learned and increase the desire forindependent learning